COMPARATIVE ANALYSIS OF ADJECTIVE DEGREES IN ENGLISH AND RUSSIAN LANGUAGES (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
This article explores the degrees of adjectives in English and Russian languages. Both languages utilize three degrees of comparison for adjectives: positive, comparative, and superlative. However, there are notable differences in the formation and usage of these degrees between English and Russian. This analysis highlights the distinct rules and patterns governing adjective degrees in English and Russian, providing insights into the structural and functional differences between the two languages. Understanding these variations can enhance language learners' proficiency and appreciation of linguistic diversity.